1045 T1-mapping and CMR feature tracking in mitral valve prolapse. (17th January 2020) - Guglielmo, M; Fusini, L; Muscogiuri, G; Baggiano, A; Loffreno, A; Baessato, F; Bonalumi, G; Zanobini, M; Alamanni, F; Pepi, M; Pontone, G
Abstract: BACKGROUND: Several studies suggest that mitral valve prolapse (MVP) can be related to sudden cardiac death, owing to sustained ventricular arrhythmias (VAs). In patients with sudden cardiac death and complex VAs, a high percentage of either left ventricle (LV) papillary muscle fibrosis or inferobasal fibrosis has been described using cardiac magnetic resonance (CMR) with late gadolinium enhancement technique (LGE). However, LGE presents several technical limitations and requires contrast agent administration. Thanks to T1 mapping (T1-map) and feature tracking (FT) techniques, CMR may identify myocardial fibrosis and deformation abnormalities respectively. We sought to demonstrate that, in patients with MVP, T1 map can accurately identify the presence of myocardial fibrosis which, being related to myocardial stiffness, is associated to abnormal deformation indexes at CMR FT strain evaluation. METHODS: Consecutive patientswith indication to mitral valve surgery for severe mitral regurgitation due to mitral valve prolapse were prospectively enrolled. CMR including Modified Look-Locker (MOLLI) sequences for T1 mapping was performed in each patient. In addition, CMR FT analysis of steady state free precession (SSFP) cine images was performed to obtain 2D global and segmental circumferential and radial strains. RESULTS: 70 consecutive patients (age: 59 ± 12) were successfully evaluated with CMR. T1 native values were significantly higher in the basal and mid LV inferolateral wall compared to the remote myocardium (1074 ± 67 vs 1046 ± 40 msec, p< 0.001). Moreover, the average radial and circumferential strains of the basal and mid LV inferolateral were significantly reduced compared to those of the remote myocardium (21.1 ± 10.4 and -12.8 ± 5.6 vs 31.6 ± 9.1 and -17.3 ± 3.6 respectively, p < 0.001). CONCLUSIONS: In patients with MVP and severe mitral regurgitation native T1 values of the LV inferolateral are higher as compared to remote myocardium and associated with reduced circumferential and radial strains. T1 mapping and CMR FT strain may be used as tools for the early identification of tissue changes in the LV inferolateral myocardial segment. Further studies are needed to evaluate if these changes are able to predict LGE development and are associated with higher risk for VAs